UMA PROPOSTA DE JOGO PARA O ENSINO DE CONGRUÊNCIAS DE NÚMEROS INTEIROS - Evaristo Liberto Nascimento Leiva (2021)
This study proposes the introduction of basic topics in Arithmetic, especially congruences, for elementary school students. The proposal aims to contribute to the complementation of Mathematics training in schools, through extracurricular activities with the use of a sequence of games. We report the experience gained with the application of the game, where students are challenged to develop strategies for solutions that become effective with the formalization of the mathematical concept.